TINJAUAN YURIDIS TERHADAP PERLINDUNGAN HUKUM KORBAN KEKERASAN SEKSUAL: IMPLEMENTASI UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL - Herwantono; Sugiarto, Agus (Jurnal De Jure Muhammadiyah Cirebon, 2025)
Sexual violence is a serious issue with widespread impacts on victims, affecting them physically, psychologically, and socially. The enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes is a significant step in providing legal protection for victims of sexual violence in Indonesia. This research employs a normative juridical method by examining relevant legislation and academic literature to analyze the implementation of the Sexual Violence Crimes Law in fulfilling the rights of victims. The objective of this study is to identify the extent to which the implementation of the Sexual Violence Crimes Law is effective in protecting victims of sexual violence and addressing existing challenges. The findings indicate that although the Sexual Violence Crimes Law provides a strong legal foundation, its implementation still faces significant obstacles such as a lack of understanding among law enforcement officials, limited supporting infrastructure, and negative societal stigma towards victims. Therefore, a collaborative effort from all parties is necessary to comprehensively maximize the fulfillment of victims' rights. Keywords: Sexual Violence Crimes Law, Victims, Sexual Violence